Assessing the feasibility of a community health worker-delivered mental health intervention for Latina immigrant women - Pérez-Solorio, S. Adriana; Gudino, Juan; Perez, Georgina; Maurer, Serena; Baquero, Barbara; Rao, Deepa; Ornelas, India J. (Frontiers in Public Health, 2025)
IntroductionLatina immigrants are at high risk for mental health concerns and also face barriers to accessing mental health resources. Community health workers are increasingly being used to provide culturally relevant mental health care in areas with a limited workforce.MethodsThis study tested an implementation strategy of training and support community health workers (CHW) to deliver Amigas Latinas Motivando el Alma (ALMA), a community-based mental health intervention to reduce depression and anxiety among Latina immigrants. We trained five CHWs to deliver the ALMA intervention at two community-based organizations in central Washington. These CHWs then offered the program to Latina immigrants (n = 37) at each of their organizations with support from our bilingual research team. We collected survey data on CHW and participant characteristics, intervention fidelity, participant attendance, satisfaction, and changes in depression (PHQ-8) and anxiety (GAD-7) pre-and post-intervention.ResultsOverall, training and supporting the CHWs to deliver the intervention was feasible. CHW completed all training sessions and delivered almost all of the program activities in the ALMA sessions. We found high participant engagement and satisfaction with the program. Mean depression scores (PHQ-8) decreased from 7.2 (mild severity) pre-intervention to 4.5 (minimal severity) post-intervention, and anxiety scores (GAD-7) decreased from 6.7 (mild severity) to 3.8 (minimal severity).DiscussionThese results indicate that training CHW may be an effective way to broaden the reach and sustainability of the program. Future research should evaluate this approach in a larger trial with a more rigorous study design.